The Risks of Social Noise Exposure in the Vulnerable Population in Slovakia - ARGALASOVA, Lubica; FILOVA, Alexandra; HIROSOVA, Katarina; VONDROVA, Diana; SAMOHYL, Martin; KRAJCOVA, Daniela; JURKOVICOVA, Jana; SEVCIKOVA, Ludmila (Archives of Acoustics, 2016)
The study is aimed to quantify the effects of social noise exposure (personal music players (PMP), events with high noise exposure) and the exposure to the other environmental noise sources in the selected sample of Slovak university students. The validated ICBEN methodology was used to assess noise annoyance. The measurement of ambient noise levels was done using hand-held sound level analyzer. There were 526 university students (143 males and 383 females, average age 23±2.2) enrolled into the study so far, 192 in the exposed housing facility to road traffic noise and 326 in the control housing facility in Bratislava. The social noise exposure was quantified and followed according to the authorized methodology of the study Ohrkan. From the total sample 416 (79.4%) students reported the use of PMP in the last week for the average time of 314 minutes. There was a significant difference in PMP use between the exposed (85.34%) and the control group (76.31%) (p = 0.01). Among PMP users 28.1% exceeded the LAV (lower action value for industry = 80 dB). The results showed the importance of road traffic and the social noise as well and the need for prevention and intervention in these vulnerable groups.